PEMANTAUAN KEMATANGAN KOMPOS DARI SAMPAH ORGANIK BERDASARKAN KARAKTERISTIK FISIK - Romisah Toijon, Romanus; Wahyudi, Reza; Putranto, Rizky (Fakultas Teknik Universitas Panca Bhakti, 2022)
Organic waste at the traditional market of Melati Puring Parit Baru, Sungai Raya District, Kubu Raya Regency, located on Jalan Adisucipto. namely cow dung and organic waste can pollute the surrounding environment. A pungent smell wafted from the cattle dung. Organic waste can be vector breeding. The litter that is scattered around the TPS is not aesthetically pleasing. The type of research carried out is experimental research with pre-experimental design research in the kind of Comparison of Four samples on a laboratory scale. The sample in this study was organic waste from the Melati Puring market, with 4 treatments. Which uses EM4, as an activator, cow dung as an activator, does not use an activator, and a combination of cow dung and EM4 as an activator. This research on a laboratory scale aims to obtain an overview of the use of organic waste to be used as compost by using Effective Microorganisms 4 (EM4) as an activator and not using an activator to see the maturity of the resulting compost in terms of physical characteristics. The results showed that the maturity of the compost was not the same, the difference was in the smell and color. There was a slight smell of livestock manure in the group that did not use the activator. The color in the group that did not use the activator was brown, but it was not as significant as in the group that used it. The maturity time of compost in the group that used the activator was 15 days, while in the group that did not use the activator it was 40 days. The community is advised to use organic waste to make compost by using a combination of cow dung and EM4 as an activator. keywords: Monitoring, composting, physical characteristics